2008
DOI: 10.1029/2008jd009907
|View full text |Cite
|
Sign up to set email alerts
|

A case study of the mesospheric 6.5‐day wave observed by radar systems

Abstract: In this paper, analysis of wind data detected by six ground‐based radar systems located in equatorial and midlatitude belts shows that a strong mesospheric 6.5‐day wave event occurred during April–May 2003. We compared the global distribution of the observed 6.5‐day wave event with the theoretical wave structure (Rossby normal mode (s, n) = (1, −2)). Additionally, we investigated several important wave characteristics to understand the mesospheric 6.5‐day wave event, i.e., wave period, vertical structure, rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 33 publications
7
39
0
Order By: Relevance
“…A wavelet analysis of radar wind measurements at lowto mid-latitudes by Jiang et al (2008) If the 5DW can be amplified by baroclinic instability (Meyer and Forbes, 1997), interannual variability of the 5DW may be associated with interannual variability of the vertical shear because baroclinic instability is associated with a strong vertical shear in the zonal wind. The vertical shear is related to the 11-year solar cycle (Fritz and Angell, 1976) and even has a multi-decadal variability (Aiyyer and Thorncroft, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A wavelet analysis of radar wind measurements at lowto mid-latitudes by Jiang et al (2008) If the 5DW can be amplified by baroclinic instability (Meyer and Forbes, 1997), interannual variability of the 5DW may be associated with interannual variability of the vertical shear because baroclinic instability is associated with a strong vertical shear in the zonal wind. The vertical shear is related to the 11-year solar cycle (Fritz and Angell, 1976) and even has a multi-decadal variability (Aiyyer and Thorncroft, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Lima et al (2005) observed the 6.5-day wave using a meteor radar at Cachoeira Paulista (23 • S, 45 • W) and found significant interannual variability in the zonal component, with maximum amplitudes occurring from winter to spring. Jiang et al (2008) employed radar winds at six low-and mid-latitude sites and concluded that enhancement of the 6.5-day wave from April to May is a global-scale phenomenon, maximizing at subequatorial latitudes in the Northern Hemisphere. Furthermore, Kishore et al (2006) employed stratospheric temperature measurements by a Rayleigh lidar at Gadanki (14 • N, 79 • E) and confirmed a stronger 6.5-day wave at lower altitudes than in the MLT.…”
Section: H Iimura Et Al: 5-day Wave Meteor Windsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum amplitudes (12-14 m s −1 ) are observed at KOT and PAM radar stations at 94 km of altitude, while moderate amplitudes are observed over the PON radar. Jiang et al (2008) observed that 6.5-day wave amplitudes were strongest between 84 and 98 km, and the maximum amplitude of ∼ 14.5 m s −1 appeared at 92 km in April-May 2004 using the Wuhan meteor radar. Furthermore, they indicated that the 6.5-day waves near the spring equinox were generally stronger than those in other seasons.…”
Section: Temporal Variability In Mean Windsmentioning
confidence: 99%
“…Furthermore, they indicated that the 6.5-day waves near the spring equinox were generally stronger than those in other seasons. A large mesospheric 6.5-day wave was seen during late April and early May 2003 by the SABER instrument aboard the TIMED satellite and the ground-based radar systems (Riggin et al, 2006;Jiang et al, 2008). They mentioned that the 6.5-day wave in the MLT region during April-May 2003 should be regarded as an atmospheric normal mode, which was amplified through sympathetic interaction with the background wind.…”
Section: Temporal Variability In Mean Windsmentioning
confidence: 99%